Business Development Evaluation of Rice Trading and Milling UD Wahyu Jaya in Sidareja District, Cilacap Regency - wahyu Indarto; Sumadi, Sumadi (Cita konsultindo, 2025)
Rice trading and milling are essential parts of the agribusiness system that support food security in various countries, particularly in agrarian regions like Indonesia. The rice milling process is a critical stage in the supply chain, where harvested paddy is processed into ready-to-consume rice. This study aims to analyze the business processes, supply chain, and challenges faced in the rice milling and distribution industry.The report aims to evaluate and develop the business operations of rice milling and rice trading in terms of sales and income to enhance the company's business programs for better growth in the highly competitive market of today. Market competition is fierce nowadays, and marketing aspects need to be improved to compete in the market. Expanding outreach with other companies is also prioritized in this business development to establish partnerships. An effective distribution system is key to ensuring the availability and affordability of rice for consumers. Proposed recommendations include the modernization of milling equipment, strengthening partnerships between farmers and entrepreneurs, and developing government policies that support market stability. These efforts are expected to enable the rice milling and trading sector to contribute more significantly to national food security.